PENGARUH WAKTU EKSTRAKSI DAUN BINAHONG (Anredera cordifolia (Tenore) Steenis) TERHADAP KEMAMPUAN DAYA HAMBAT BAKTERI Escherichia coli UNTUK PEMBUATAN HAND SANITIZER - Susanty Susanty; Sri Anastasia Yudhistirani (JURNAL KONVERSI, 2018)
Binahong leaf extract (Anredera cordifolia (Tenore) Steenis) contains active compounds such alkaloids, flavonoids, terpenoids, and saponins as antibiotic materials that can be used in the manufacture of antiseptic gel hand sanitizers. The purpose of this research is to know the effect of extraction time of binahong leaf to the capability of growth of Escherichia coli (E. Coli) bacteria. Variable times of exstractions are 0,5; 1; 1.5; 2; and 2.5 hours. Phytochemical qualitative test was conducted to determine the presence of alkaloids, flavonoids, terpenoids, and saponins in the binahong leaf extract. Furthermore, dilution of the results of rendement of binahong leaf extract respectively by 5% to test its inhibitory power to the growth of E. coli bacteria. The results showed that the yield of rendemen obtained by extraction time variable was 1.64%; 3.72%; 5.56%; 13.74%; and 13.98% are shown through the equation y = 3.47 x - 2.682 with the value R2 = 0.9049. Data from all five samples showed that samples with extraction time of 0.5; 1; and 1.5 hours had no inhibitory effect on E. coli bacteria growth, but samples with 2 and 2.5 hours extraction time had a resistance diameter of 14.5 and 18.5 mm. The sample which has the greatest inhibitory is subsequently used to make the hand sanitizer antiseptic gel. The product test analysis consists of organoleptic test and pH value determination, homogeneity, dispersion and viscosity. The results showed that the pH value obtained was 6.23, the homogeneity of the product can be seen from the absence of material that still agglomerates, the dissolving power of the research product is 5.5 cm, and the viscosity of the research result is 2080 mPs.